Benefits of Affective Pedagogical Agents in Multimedia Instruction - Wang, Yanqing; Feng, Xiaowei; Guo, Jiangnan; Gong, Shaoying; Wu, Yanan; Wang, Jing (Frontiers in Psychology, 2022)
The goal of the present study is to explore whether the affective states (happy or neutral) of a pedagogical agent (PA) in an online multimedia lesson yields different learning processes and outcomes, and whether the effects of affective PAs depend on the learners’ emotion regulation strategies and their prior knowledge. In 3 experiments, undergraduates were asked to view a narrated animation about synaptic transmission that included either a happy PA (smiling expression and enthusiastic voice) or a neutral PA (neutral expression and calm voice) and subsequently took emotions, motivation, cognitive outcomes tests. Across three experiments, the happy PA group reported more positive emotions (ds = 0.70, 0.46 and 0.60) and higher level of motivation (ds = 0.76, 0.49 and 0.51) than the neutral PA group. However, adding a happy PA to the screen did not improve learning performance. In addition, in Experiment 2, learners’ usage of emotion regulation strategies moderated the effectiveness of affective PA on positive emotions in learners. Specifically, happy PAs increased the positive emotions of students who used expressive suppression strategy (d = 0.99) but not those who used cognitive reappraisal strategy (d = 0.13). In Experiment 3, the effectiveness of affective PAs was not moderated by learners’ prior knowledge. Results support the cognitive affective theory of learning with media (CATLM) that students are happier and more motivated when they learn from happy PAs than from neutral PAs.